137k views
5 votes
Yeah that’s okay I got a lot done and I’m not taking them to the park

Yeah that’s okay I got a lot done and I’m not taking them to the park-example-1
User Ian M
by
4.7k points

1 Answer

6 votes

C. - 2 / 5

Step-by-step explanation:

To find k(1), you need to replace x with 1 in the equation k(x)


\begin{gathered} \frac{3x\text{ - 5}}{2x\text{ + 3}}\text{ => }\frac{3*1\text{ - 5}}{2*1\text{ + 3}}\text{ } \\ \text{=>}\frac{3\text{ - 5 }}{2\text{ + 3}}\text{ => }\frac{-\text{ 2}}{5}\text{ =- }(2)/(5) \\ \end{gathered}

User Mohammed Jhosawa
by
5.1k points